2019
DOI: 10.1200/jco.2019.37.15_suppl.e12057
|View full text |Cite
|
Sign up to set email alerts
|

Short versus long duration of adjuvant trastuzumab (T) in HER2+ breast cancer: A systematic review and meta-analysis of randomized controlled trials (RCTs).

Abstract: e12057 Background: Several RCTs have evaluated a shorter duration of T ( < 12 months) with hopes of similar efficacy, reduced cardiotoxicity, cost and burden of treatment. Of the 5 major studies, PERSPHONE showed that 6 months was non-inferior compared to 12 months. However, four additional studies of shorter duration failed to demonstrate non-inferiority. Therefore, we performed an updated systematic review and a meta-analysis to assess the optimal duration of adjuvant T. Methods: MEDLINE, EMBASE, Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Admittedly, our meta-analysis is not the first to compare short durations vs. 12 months of trastuzumab, and there are at least six similar meta-analyses or systematic reviews so far (26,27,(36)(37)(38)(39). However, these similar studies were found to have some serious limitations.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Admittedly, our meta-analysis is not the first to compare short durations vs. 12 months of trastuzumab, and there are at least six similar meta-analyses or systematic reviews so far (26,27,(36)(37)(38)(39). However, these similar studies were found to have some serious limitations.…”
Section: Discussionmentioning
confidence: 96%
“…Firstly, the two studies presented at ASCO 2019 provided only brief abstracts rather than detailed full-text articles, and they may lack some important information (36,37). Secondly, most similar studies compared short durations vs. 12 months of trastuzumab, but we concentrated on 6 months of trastuzumab rather than several different short durations (26,27,(36)(37)(38)(39). There may be substantial bias if 6 months and other different short durations are combined arbitrarily.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations